Factors affecting micropropagation in Vanilla (Vanilla × Tahitensis J. W. Moore) from node explants - Nguyen, Ly Ngoc Han; Nghi, Khac Nhu; Tran, Thi Kim Nhu; Trinh, Ngoc Ai (Hue University Journal of Science: Natural Science, 2025)
This study aims to develop a comprehensive micropropagation protocol for the Vanilla plant (Vanilla × tahitensis J. W. Moore). In vitro shoots of Vanilla were cultured on the MS (Murashige and Skoog) medium supplemented with growth regulators and gelling agents to assess shoot multiplication rates and root formation capability after 10 weeks. The MS medium with 1 mg/L BAP, 0.5 mg/L Kn, and 10% coconut juice produced 4.98 shoots per sample, the best shoot multiplication rate. Shoots reached an average height of 3.98 cm, with 4.25 leaves per sample. Gelrite was the most effective gelling agent for shoot development, resulting in the most significant shoot height (4.04 cm) and the most leaves (7.67 leaves per sample). The MS medium with 1 mg/L IBA and 0.5 mg/L NAA optimised root formation, producing 3.11 roots per sample, with an average root length of 5.11 cm. After 3 weeks of cultivation in decomposed coconut fibre, all seedlings survived with an average plant height of 8.39 cm and an average of 6.52 leaves per plant.